Konsekuensi Berlebihan dalam Beragama Perspektif Tafsir Al-Qur’an: Sebuah Kajian Tematik - Alfani, Ilzam Hubby Dzikrillah (Lembaga Yasin AlSys, 2023)
This study aims to explain and reveal verses related to Extremism (ghuluw) in religion and its consequences from the perspective of Tafsir Al-Qur'anul Majid An-Nur by M. Hasbi Ash-Shiddieqy. This study used a qualitative approach using content analysis methods. Ghuluw is an attitude of extremism in religion. Phenomena that often occur in social life. The ghuluw attitude is not liked by Allah SWT. Because it has exceeded the limit that has been determined by Allah through Islamic religious shari'ah. In the Al-Qur'an there are two words ghuluw in the form of a command verb (fi'il amr) which indicates a prohibition (nahyi) in Q.S An-Nisa verse 171 and Al-Midah 77, which aims His people to avoid bad attitudes rebuked by Allah SWT. This study concludes that ghuluw is an attitude that prioritizes passions and overrides reason. Whereas ghuluw in religion means a careless attitude that tends to be excessive in religion falsely. This attitude is not prescribed and is not justified in religion. This attitude has very dangerous consequences, including the cause of disbelief and being kept away from the grace of Allah SWT.